Foreign direct investments and International Financial Reporting Standards Adoption in Africa - Emeni, Francis Kehinde (Ushus Journal of Business Management, 2014)
This study examines the relationship between Foreign Direct Investments (FDI) and International Financial Reporting Standards (IFRS) adoption in Africa. Data were collected from Forty-six countries in Africa out of the fifty four countries making up the African continent; where it was reported in extant literature that only 54% of African countries have adopted the IFRS product. The Ordered Logistic Regression (OLR) technique under the E-view 7.0 software was used to analyse the data collected. The study reveals that foreign direct investment has a positive but not significant relationship with adoption of IFRS in Africa. This not significant relationship is attributable to the scanty flow of FDI to Africa. Based on this result, it was recommended that policy effort should be put in place to enhance the flow of foreign direct investment into the African economy, may be by creating an enabling environment free from corruption and inadequate security of life and properties. More of this will stir economic/capital market growth and deepen the need to practice or adopt the International Financial Reporting Standards (IFRS) in Africa